Influência da estrutura anatômica de Brosimum rubescens Taub. Moraceae (Pau-rainha) no processo de microdistribuição do CCA -A - Campos, Ceci Sales (Acta Amazonica, 2020)
In the present study, the wood treatability of the Amazon species Brosimum rubescens Taub., Moraceae (pau-rainha) was evaluated. The tests were carried out on three different positions of the tree stem (lower end, middle and upper end) with CCA type A at 2% concentration, using the Full-Cell process, also known as "Bethell" process. The data showed that the sapwood is moderately difficult to preserve, whereas the heartwood is refractory. The results of absorption at different positions of the tree stem did not present significant differences. There was a significant difference between sapwood and heart-wood, with the retention ranging from 7,95 to 8,84 kg/m3 for sapwood and from 0,13 to 0,27 kg/m3 for heartwood. Although the vessels are considered structures of major importance related to conduction, the fibres played a relevant role in the process of preservative distribution. The rays and the axial parenchyma, even in the sapwood, were not efficient due to extractive deposits present in these elements. These results suggest that the refractory property of the heartwood, as well as the limited permeability of the sapwood of this specie is related to the extractive contents present in the wood, and especially due to the presence of tyloses inside the vessels.